Relative salinity tolerance of warm season turfgrass species. - Uddin, Md. Kamal; Juraimi, Abdul Shukor; Ismail, Mohd Razi; Othman, Radziah; Abdul Rahim, Anuar (Triveni Enterprises, Lucknow (India), 2011)
Fresh water coupled with soil salinization in many areas has resulted in an increased need for screening of salt tolerant turf grasses. Relative salinity tolerance of eight warm season turfgrass species were examined in this study in sand culture. Grasses were grown in a glasshouse irrrigated with either distilled water or saline sea water adjusted to 24, 48 or 72 dSm -1. Salt tolerances of the grasses were assessed on the basis of their shoot and root growth leaffiring and turf quality. Regression analysis indicated that Zoysia japoaica (Japanese lawn grass) (JG) Stenotaphrum secundatum (St. Augustine) (SA), Cynodon dactylon (satiri) (BS) Zoysia teneuifolia (Korean grass) (KG) Digitaria didactyla (Serangoon grass) (SG) Cynodon dactylon (Tifdwarf) (TD) Paspalum notatum (Bahia grass) (BG) and Axonopus compressus(Pearl blue) (PB) suffered a 50%shootgrowth reduction at 36.0, 31.8, 30.9, 28.4, 26.4, 25.7, 20.0 and 18.6 dSm -1 of salinity respectively and a root growth reduction at 44.9, 43.7, 33.4, 31.0, 29.5, 27.5, 21.5 and 21.4 dSm -1 of salinity respectively Leaf finng and turf quality of the selected species as a whole were also found to be affected harmoniously with the change in root and shoot growth On the basis of the expenmental results the selected species were ranked for salinity tolerance as JG>SP>BS>KG> SG>TD>BG>PB.